Cu,Ce/mordenite coatings on FeCrAl-alloy corrugated foils employed as catalytic microreactors for CO oxidation - Pérez, Nicolas C. (2013)
The aim of this work was to study different strategies for the synthesis of mordenite coatings on thin FeCrAl alloy foils in order to obtain adherent, stable and homogeneous films for their use as catalytic microreactors. For this purpose, the substrate pretreatments and growth conditions of the films by secondary synthesis were investigated. The best results were obtained by applying a brief calcination of the foils at 700 ºC that developed a smooth alumina film with hydrophilic properties, followed by immersion in a 0.4 wt.% aqueous solution of the cationic polymer poly-(diallyldimethilammoniumchloride), PDDA. The subsequent seeding with diluted nanocristal suspensions (2 g L) of Na-mordenite allowed the development of zeolite films with the desired properties and the additional benefit of a marked preferential growth on the metallic surface at the expense of a negligible growth within the synthesis solution. Finally, homogenous zeolite films were obtained in micro-corrugated foils, after which Cu and Ce were incorporated as catalytic ingredients and used in a microreactor for the CO oxidation reaction under different conditions.